Characterization of Milkisin, a Novel Lipopeptide With Antimicrobial Properties Produced By Pseudomonas sp. UCMA 17988 Isolated From Bovine Raw Milk - Schlusselhuber, Margot; Godard, Justine; Sebban, Muriel; Bernay, Benoit; Garon, David; Seguin, Virginie; Oulyadi, Hassan; Desmasures, Nathalie (Frontiers in Microbiology, 2018)
Biosurfactants such as lipopeptides are amphiphilic compounds produced by microorganisms such as bacteria of the genera of Pseudomonas and Bacillus. Some of these molecules proved to have interesting antimicrobial, antiviral, insecticide and/or tensio-active properties that are potentially useful for the agricultural, chemical, food and pharmaceutical industries. Raw milk provides a physicochemical environment that is favorable to the multiplication of a broad spectrum of microorganisms. Among them, psychrotrophic bacterial species, especially members of the genus Pseudomonas, are predominant and colonize milk during cold storage and/or processing. We isolated the strain Pseudomonas sp. UCMA 17988 from raw cow milk, with antagonistic activity against Listeria monocytogenes, Staphylococcus aureus and Salmonella enterica Newport. Antimicrobial molecules involved in the antagonistic activity of this strain were characterized. A mass spectrometry analysis highlighted the presence of 4 lipopeptides isoforms. The major isoform (1409 m/z), composed of 10 carbons in the lipidic chain, was named milkisin C. The three other isoforms detected at 1381 m/z, 1395 m/z and 1423 m/z, that are concomitantly produced, were named milkisin A, B and D, respectively. The structure of milkisin, as confirmed by NMR analyses, is closely related to amphisin family. Indeed, the peptidic chain was composed of 11 amino acids, 6 of which are conserved among the family. In conclusion, Pseudomonas sp. UCMA 17988 produces new members of the amphisin family which are responsible for the antagonistic activity of this strain.